1996
DOI: 10.1097/00000478-199608000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cutaneous Infiltrates of B-cell Chronic Lymphocytic Leukemia

Abstract: The clinical and histopathologic features of specific skin infiltrates in patients with B-cell chronic lymphocytic leukemia (B-CLL) have rarely been reported in detail. In this study we analyzed the clinical, histopathologic, immunophenotypic, and molecular features of 84 skin lesions from 42 patients (M:F = 1.3:1; mean age, 66.0 years; range, 42-83 years) with specific cutaneous manifestations of B-CLL. The duration of B-CLL before skin manifestations varied from 0 to 142 months (mean, 39 months). In seven pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
185
0
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(204 citation statements)
references
References 22 publications
13
185
0
6
Order By: Relevance
“…Cutaneous infiltrations by CLL/SLL have been previously described at sites that are characteristic of borrelial lymphocytoma (ear lobe, nipple, scrotum), a Borrelia burgdorferi-associated skin manifestation that involves polyclonal lymphoid hyperplasia [4,6,7]. In fact, the particular site of involvement was very suggestive of an association with the infection in our case.…”
Section: Histopathological Haematological Laboratory and Imaging Fisupporting
confidence: 63%
See 1 more Smart Citation
“…Cutaneous infiltrations by CLL/SLL have been previously described at sites that are characteristic of borrelial lymphocytoma (ear lobe, nipple, scrotum), a Borrelia burgdorferi-associated skin manifestation that involves polyclonal lymphoid hyperplasia [4,6,7]. In fact, the particular site of involvement was very suggestive of an association with the infection in our case.…”
Section: Histopathological Haematological Laboratory and Imaging Fisupporting
confidence: 63%
“…Skin involvement is a rare initial presentation of the disease. One study showed that skin infiltration by tumour cells was the initial manifestation in 7 patients (16.7%) from a series of 42 patients with B-CLL/SLL [4]. Borrelia burgdorferi infection has been linked to skin manifestations of CLL/SLL [5].…”
mentioning
confidence: 99%
“…Auch beim rezidivfreien Überleben und der mittleren Zeitdauer der kompletten Remission ergaben sich keine statistisch signifikanten Unterschiede [28]. Andere Arbeitsgruppen konnten keinen direkten Zusammenhang zwischen dem Ausmaß der Hautinfiltration bei LC oder einem spezifischen histologischen Infiltrationsmuster und einer prognostischen Bedeutung herstellen [27,67]. Die molekularpathologische Diagnostik verschiedener Genmutationen (z.…”
Section: Differenzialdiagnosenunclassified
“…1,8 The commonest presentation is with multiple patches. [9][10][11][12] An unusual but well-documented presentation is the occurrence of specific B-CLL infiltrates in the vicinity of epithelial and nonepithelial lesions, including squamous cell carcinoma, keratoacanthoma, melanoma, Merkel cell carcinoma, dermatofibroma to name but a few. [13][14][15][16][17][18] Additionally, an association of B-CLL and various cutaneous T-cell lymphomas has been documented, including MF, Sézary syndrome, peripheral T-cell lymphoma involving the skin, and natural killer-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%